Longitudinal Associations Between Anxiety, Pain Catastrophizing, and Treatment Outcomes in Complex Pediatric Chronic Pain - (:unkn) unknown (My University, 2014)
Anxiety and pain catastrophizing have been identified as factors that may predispose an individual to developing chronic pain and influence functional outcomes. The purpose of this study was to investigate the longitudinal associations of anxiety and pain catastrophizing with functional outcomes in a sample of youth seeking treatment for chronic pain. The current study aimed to expand upon recent literature by examining the relative contributions of both anxiety and pain catastrophizing to important functional outcomes (pain, functional disability, and health-related quality of life [HRQOL]) in a longitudinal design. Participants included 725 youth (69% females, 75% Caucasian) ranging in age from 8 to 18 who received services at an outpatient interdisciplinary pain clinic for complex chronic pain. Data were gathered from a retrospective chart review of questionnaires completed by families at their intake appointment at the pain clinic (baseline), one month, and three month follow-up. Families were mailed a packet including questionnaires for the youth with chronic pain and their parents/guardians. Youth self-reported questionnaires regarding anxiety, pain catastrophizing, functional disability, and HRQOL were examined. Higher anxiety and pain catastrophizing were related to 1) higher pain intensity, 2) higher functional disability, and 3) lower HRQOL at baseline after controlling for demographic characteristics and pain characteristics. Changes in anxiety and pain catastrophizing contributed unique variance in longitudinally predicting later pain, functional disability, and HRQOL. The results of this study support targeting anxiety and pain catastrophizing in treatment of pediatric chronic pain. It will be important for future research to consider models including mediators of these relationships and moderators of functional outcomes.
Keywords: Anxiety; Children; Chronic Pain; Functional Disability; Pain Catastrophizing; Quality of Life